2008
DOI: 10.1038/ajh.2007.34
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Linkage Analysis of Pulse Pressure in American Indians: The Strong Heart Study

Abstract: The signal on 7p15.3 overlaps positive findings for pulse pressure among Utah population samples, suggesting that this region may harbor gene variants for blood pressure related traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
(30 reference statements)
0
8
1
Order By: Relevance
“…The genetic locus we found to be linked to carotid artery size in this study has also been shown to be associated with systolic and diastolic blood pressure in Nigerian families (35) and with body mass index in the NHLBI Family Heart Study (36). While it is possible that the attenuation of the linkage signal we observed after full covariate adjustment that included blood pressure and body size could be attributed to the association of this locus to blood pressure and body size, we did not find any linkage evidence at this locus with blood pressure or body mass index in the American Indian SHFS participants (3739). …”
Section: Discussioncontrasting
confidence: 67%
“…The genetic locus we found to be linked to carotid artery size in this study has also been shown to be associated with systolic and diastolic blood pressure in Nigerian families (35) and with body mass index in the NHLBI Family Heart Study (36). While it is possible that the attenuation of the linkage signal we observed after full covariate adjustment that included blood pressure and body size could be attributed to the association of this locus to blood pressure and body size, we did not find any linkage evidence at this locus with blood pressure or body mass index in the American Indian SHFS participants (3739). …”
Section: Discussioncontrasting
confidence: 67%
“…A recently published study has also shown linkage on chromosome 7p15 (LOD 3.3) to pulse pressure, a measure of central arterial stiffness and a predictor of cardiovascular mortality [33]. None of the genomewide association studies (GWAS) of atherosclerosis have published association with variants on chromosome 7p.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a linkage for the right carotid artery diastolic and systolic lumen diameter was also detected on chromosome 9 at 154 cM in the Oklahoma participants [ 63 ]. Linkages of chromosome 7p19q with pulse pressure, glucose/insulin/obesity factor to chromosome 4, the dyslipidemia factor to chromosome 12, and the blood pressure factor to chromosome 1 were also identified among SHFS participants [ 64 , 65 ].…”
Section: Genetics Heritability and Other Risk Factors Contributementioning
confidence: 99%